Case Report: Virtual reality training for phantom limb pain after amputation - Yoshimura, Manabu; Kurumadani, Hiroshi; Hirata, Junya; Senoo, Katsutoshi; Hanayama, Kozo; Sunagawa, Toru; Uchida, Kosuke; Gofuku, Akio; Sato, Kenji (Frontiers in Human Neuroscience, 2023)
Several reports have demonstrated the effectiveness of neurorehabilitation, such as mirror therapy or virtual reality, in treating phantom limb pain (PLP). This case study describes the effect of virtual reality training (VRT) on severe, long-term PLP and upper limb activity on the amputated side in a patient who underwent digit amputation nine years prior.A woman in her 40s underwent amputation of 2-5 fingers nine years prior due to a workplace accident. She experienced persistent pain in the palms of her hand near the amputation sites. A single case design (ABA'B') was applied. Periods A and A' were set as periods without VRT intervention, and Periods B and B' were set as periods with VRT intervention. Periods A, B, A', and B' lasted 4, 10, 8, and 10 weeks, respectively. VRT was a task during which visual stimulation and upper limb movements were linked. The task consisted of catching a rolling ball in the display with a virtual hand, operated with both hands using a controller. VRT was performed once every 2-4 weeks for 30 minutes. Pain intensity was assessed using the short-form McGill Pain Questionnaire-2. Bilateral upper limb activity was measured continuously for 24 hours using a triaxial accelerometer attached to the right and left wrist joints.The pain intensity was 147/220 points during Period A, 128 points during Period B, 93 points during Period A', and 100 points during Period B', showing a gradual decrease. Upper limb activity occurred mainly on the intact side during Periods A and B, whereas the activity on the amputated side increased two-fold after Period A', and both upper extremities were used equally.